Pengaruh Media Sosial Terhadap Niat Beli Produk Trifthing Ditoko Texar Store Surabaya - Fikri, Kanzul; Nindya Kartika Kusmayati; Yourini Erawati (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
The increasing number of people considering social media applications as crucial elements in their daily lives, observing the tendency of individuals to use virtual platforms such as Facebook, Instagram, TikTok, and Twitter. This study involved 37 respondents. Data collection was conducted using snowball sampling method, and analysis was performed using PLS-Structural Equations Modelling (SEM). PR has a significant effect on purchase intention by (0.416) with a t-statistic result (2.468 > 1.96) or p-value (0.014 < 0.05). Changes in PR will significantly develop customer purchase intention. The PI factor also significantly influences purchase intention (0.562) with a t-statistic result (4.637 > 1.96) or p-value (0.000 < 0.05). However, changes in PI will significantly increase customer purchase intention. PC has no significant effect on purchase intention by (-0.096) with a t-statistic result (0.565 < 1.96) or p-value (0.572 > 0.05). Any changes in PC do not influence increasing customer purchase intention.